Anammox start-up strategies: the use of local mixed activated sludge seed versus Anammox seed - KOCAMEMİ, BİLGE; SEMERCİ, NESLİHAN (IWA PUBLISHING, 2018)
The start-up period of Anammox systems is still a big challenge due to the unavailability of large volumes of slowly growing Anammox seed locally in most countries. This study aims to evaluate the effects of seeding strategy on the start-up and enrichment period of Anammox systems by monitoring both process performance and microbial population dynamics. Two different seeding strategies, the use of mixed activated sludge culture from a local STP and the use of enriched Anammox culture transported from abroad, were comparatively studied in SBR systems operated for 410 days. The enriched Anammox seed from abroad inhibited seriously during transportation. Anammox activity re-started after 195 days' recovery period. An active Anammox culture was successfully enriched within 95 days from a local activated sludge source without seeding any Anammox. The Anammox population reached levels of 10(11) copies/ng at the end of 410 days' enrichment period. Based on FISH, Ca. Brocadia anammoxidans and Ca. Scalindua species were dominant in the enriched culture. The maximum TNRR was observed as 430 mg N/day. DGGE analyses revealed a drastic change in the microbial community (56%) with Anammox enrichment. Phylogenetic analysis demonstrated a significant decrease in phylotype Proteobacteria and increase in phylotypes Planctomycetes, Chloroflexi and Acidobacteria with enrichment.
Keywords: anaerobic ammonium oxidation (Anammox); enrichment; molecular techniques; nitrogen removal; seeding strategy; start-up; ANAEROBIC AMMONIUM OXIDATION; ENRICHMENT; BACTERIA; EXPERIENCES; REACTOR; GENES; SBR